A Practical, One-Clinic Visit Protocol for Pharmacokinetic Profile Generation with the ADVATE myPKFiT Dosing Tool in Severe Hemophilia A Subjects - Blanchette, Victor S; Zunino, Laura; Grassmann, Viviane; Barnes, Chris; Carcao, Manuel D; Curtin, Julie; Jackson, Shannon; Khoo, Liane; Komrska, Vladimir; Lillicrap, David; Morfini, Massimo; Romanova, Gabriela; et al. (Thrombosis and haemostasis, 2021)
Standard pharmacokinetic (PK) assessments are demanding for persons with hemophilia A, requiring a 72-hour washout and 5 to 11 timed blood samples. A no-washout, single-clinic visit, sparse sampling population PK (PPK) protocol is an attractive alternative. Here, we compared PK parameters obtained with a traditional washout, 6-sampling time point PPK protocol with a no-washout, single-clinic visit, reverse 2-sampling time point PPK protocol in persons with severe hemophilia A (SHA) receiving ADVATE. A total of 39 inhibitor-negative males with SHA (factor VIII activity [FVIII:C] < 2%) were enrolled in a prospective sequential design PK study. Participants completed a washout, 6-sampling time point PPK protocol as well as a no-washout, reverse 2-sampling time point protocol, with samples taken during a single 3-hour clinic visit 24 hours post home infusion of FVIII and then 3 hours post infusion in clinic. FVIII:C levels were analyzed by one-stage and chromogenic assays; blood group and von Willebrand factor antigen (VWF:Ag) were determined; and PK parameters were analyzed using the ADVATE myPKFiT dosing tool. There was moderate to almost perfect agreement for the PK parameters obtained with the 2- and the 6- point PPK protocols using a one-stage FVIII:C assay and a substantial to almost perfect agreement using a chromogenic FVIII:C assay. Significant associations between specific PK parameters and blood group and VWF:Ag were observed. The no-washout, single-clinic visit, reverse 2-sampling time point PPK protocol can be used in the routine clinical setting since it demonstrates sufficient accuracy compared with the more demanding and less practical washout, 6-sampling time point PPK protocol in persons with SHA receiving ADVATE.
Keywords: Drug Monitoring; ambulantní péče; Humans; lidé středního věku; dítě; monitorování léčiv; Predictive Value of Tests; Child; Models, Biological; Aged; mladý dospělý; dospělí; senioři; lidé; hemofilie A; hemokoagulace; Factor VIII; předškolní dítě; Adult; klinické protokoly; Ambulatory Care; Canada; Kanada; Male; Middle Aged; prediktivní hodnota testů; Blood Coagulation; Adolescent; Czech Republic; biologické modely; Young Adult; faktor VIII; koagulancia; Coagulants; Clinical Protocols; Česká republika; mužské pohlaví; prospektivní studie; Child, Preschool; Hemophilia A; Austrálie; Australia; mladiství; Prospective Studies